Long-lasting antinociceptive spinal effects in primates of the novel nociceptin/orphanin FQ receptor agonist UFP-112 - Eric Hu; Girolamo Caló; Remo Guerrini; Mei‐Chuan Ko (2009)
Chemical modifications of nociceptin/orphanin FQ (N/OFQ) peptide that result in increased potency and resistance to degradation have recently lead to the discovery of [(pF)Phe4Aib7Arg14Lys15]N/OFQ-NH2 (UFP-112), a novel N/OFQ peptide (NOP) receptor agonist. The aim of this study was to investigate the pharmacological profile of intrathecally administered UFP-112 in monkeys under different behavioral assays. Intrathecal UFP-112 (1–10 nmol) dose-dependently produced antinociception against an acute noxious stimulus (50 °C water) and capsaicin-induced thermal hyperalgesia. Intrathecal UFP-112-induced antinociception could be reversed by a NOP receptor antagonist, J-113397 (0.1 mg/kg), but not by a classic opioid receptor antagonist, naltrexone (0.03 mg/kg). Like intrathecal morphine, UFP-112 produced antinociception in two primate pain models with a similar magnitude of effectiveness and a similar duration of action that last for 4–5 h. Unlike intrathecal morphine, UFP-112 did not produce itch/scratching responses. In addition, intrathecal inactive doses of UFP-112 and morphine produced significant antinociceptive effects when given in combination without increasing scratching responses. These results demonstrated that intrathecal UFP-112 produced long-lasting morphine-comparable antinociceptive effects without potential itch side effect. This study is the first to provide functional evidence that selective NOP receptor agonists such as UFP-112 alone or in conjunction with morphine may improve the quality of spinal analgesia.